Seasonal Dataset of DO, δ^1?ODO and Biogeochemical Parameters in the Danube River (2023–2024) - Jan Maier; Anna-Neva Visser; Christina Martina Schubert; Simon Thomas Wander; Johannes Arthur Barth (PANGAEA, 2025)
This dataset contains dissolved oxygen (DO) concentrations, stable oxygen isotope ratios of DO (δ^1?ODO), particulate organic carbon (POC) concentrations, and respiration/photosynthesis (R/P) ratios, along with corresponding parameters (temperature, δ^1?OH2O, nitrate) collected from the Danube River and its key tributaries during five seasonal sampling campaigns in 2023 and 2024. Water samples were collected using a weighted 2 L sampling bottle submerged 1–2 meters below the surface, with sampling conducted from the river center via bridges or passenger boats, and occasionally from the riverbank. In situ temperature measurements were taken with a multiparameter instrument (HQ40d, HACH™, Loveland, CO, USA). δ^1?ODO was analyzed using a modified automated equilibration system (Gasbench II, ThermoFisher Scientific™) coupled to a DELTA V Advantage isotope ratio mass spectrometer (IRMS, ThermoFisher Scientific™). This dataset captures seasonal variations in DO dynamics and provides valuable insights into oxygen sources and sinks within the Danube River. The data support the study of biogeochemical cycling in large river systems and can inform ecosystem management and conservation strategies in the face of environmental and climate change.